(untitled) (Journal of Management and Educational Sciences, 2025)
The aim of this research is to examine the relationship between teacher autonomy and classroom management styles according to teachers’ opinions. Relational screening model was used in the research. In the first finding of the research; classroom management styles and teacher autonomy levels are above average. As a result of the analysis; men’s perceptions of classroom management styles were found to be higher than women. On the other hand, it was revealed that teacher autonomy perceptions did not change according to women and men. In the examination made according to age groups; it was found that the difference between teacher autonomy and the arithmetic means of age groups was statistically significant. Accordingly, it was concluded that the perception of teacher autonomy of the 31-40 age group was higher than the 41-50 age groups. The difference between the arithmetic means of classroom management styles and age groups was found to be statistically significant. Accordingly, it was concluded that the perception of classroom management styles of the 31-40 and 41-50 age groups was higher than the 20-30 age groups. On the other hand, it was revealed that teachers’ perceptions of teacher autonomy and classroom management styles did not change according to being married or single. In the examination made according to educational status; It was found that the perception of autonomy of teachers with a master’s degree was higher than that of teachers with a bachelor’s degree. On the other hand, it was found that there was no difference in their perceptions of classroom management styles according to their educational background. In the examination made according to professional experience; the difference between the arithmetic means of teacher autonomy and professional experience groups was not found to be statistically significant. However, the difference between the arithmetic means of classroom management styles and professional experience groups was found to be statistically significant. Accordingly, it was concluded that the perception of classroom management styles of the group between the ages of 17-24 was higher than the groups between the ages of 1-8 years. On the other hand, the difference between the arithmetic means of the institution type groups where the perceptions of teacher autonomy and classroom management styles were applied was not found to be statistically significant. Finally, within the scope of the research, a significant, low-level and positive relationship was found between the general dimensions of teacher autonomy and classroom management styles, while teachers’ perceptions of autonomy significantly predicted their perceptions of classroom management styles. In other words, a 100-unit increase in the dimension of teachers’ autonomy increased their perceptions of classroom management styles by 23.7%.